THE ROLE OF ISLAMIC SCHOOL LIBRARIES IN ENHANCING STUDENTS’ READING INTEREST: A STUDY AT MTSN 1 LANGKAT - Syahputri, Leli; Halimah; Puspita, Adelia; Suhenni, Enni; Pandiangan, Enda Lovita (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores the role of the school library in enhancing students’ reading interest. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation to examine library activities, reading habits, and available collections. Findings reveal that the library plays a significant role in promoting reading culture, though its function is not yet optimal due to limited space, a lack of updated collections, and librarians’ multiple responsibilities. Despite these constraints, the library remains an essential learning resource for students who demonstrate consistent reading habits. Factors that most influence students’ reading interest include collection diversity, room comfort, regular literacy programs, and support from teachers and librarians. Challenges such as competition with gadgets and limited book variety can be addressed through new acquisitions, donation programs, and digital resource utilization. Overall, well-managed libraries supported by all school elements effectively foster students’ reading culture. Penelitian ini bertujuan untuk mengkaji peran perpustakaan sekolah dalam meningkatkan minat baca siswa. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi untuk mengetahui aktivitas perpustakaan, kebiasaan membaca siswa, serta koleksi yang tersedia. Hasil penelitian menunjukkan bahwa perpustakaan memiliki peran penting dalam menumbuhkan budaya membaca, meskipun fungsinya belum optimal karena keterbatasan ruang, koleksi buku yang kurang mutakhir, dan tugas ganda pustakawan. Meskipun demikian, perpustakaan tetap menjadi sumber belajar utama bagi siswa yang memiliki kebiasaan membaca secara konsisten. Faktor yang paling berpengaruh terhadap peningkatan minat baca antara lain keberagaman koleksi, kenyamanan ruang, kegiatan literasi rutin, serta dukungan guru dan pustakawan. Hambatan seperti persaingan dengan gawai dan keterbatasan koleksi dapat diatasi melalui pengadaan buku baru, program donasi, serta pemanfaatan sumber digital. Secara keseluruhan, perpustakaan yang dikelola dengan baik dan mendapat dukungan seluruh elemen sekolah mampu menumbuhkan budaya membaca di kalangan siswa.